The Influence of Investment Decisions, Dividend Policies, and Financing Decisions on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Indah Saputri; Sulastri; Shelfi Malinda (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze and examine the effect of investment decisions, dividend policies, and financing decisions on company value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2024. The population in this study consisted of 228 manufacturing companies, with a sampling technique using purposive sampling, resulting in 38 sample companies with a total of 266 observations over seven years of observation. The type of data used was secondary data. The analysis technique used multiple linear regression analysis with classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results show that simultaneously, investment decisions, dividend policies, and financing decisions have a significant effect on company value. Partially, investment decisions have a negative effect on company value, while dividend policies and financing decisions have a positive effect on company value in manufacturing companies listed on the IDX.2.